HADIS TENTANG PEDULI LINGKUNGAN - Mubarok, Said (AL-ISHLAH: Jurnal Pendidikan, 2016)
Islam forbids Muslims to abandon a soil. Islam also advises people to give excess water to other people who need the water to maintain their soil. Rasulullah SAW ordered to hold the land for people who do not want to rent or give the land to others. He also encourages his people to plant trees. Prophet also forbade us to urinate in stagnant water. All the suggestion and prohibition have a goal to improve people life.